Knowledge of Urban Population Regarding Diabetes Mellitus and its Complication: A Community Based Study - Chaurasia, Nitendra; Thapa, Bijay; Patil, Bhimagonda H; Khandekar, Sagar; Angolkar, Mubashir; Narasannavar, Aswini; Wantamutte, AS; Karikatti, Shobha S (Journal of Nobel Medical College, 2014)
Aim: To assess the knowledge on diabetes among diabetic patients of urban poor. Background: Diabetes has been a major threat to public health as 3.2 million deaths are attributed to diabetes every year. The management of diabetes depends on knowledge of patient, self care activities and knowledge on symptoms and complications. Materials and methods: The study was carried out in the Urban Health Center area of Belgaum. The knowledge on diabetes, signs or symptoms and complications was assessed among diabetic patients, by using scoring system. Data were analyzed using percentages, proportions and statistical test (chi-square test) was used for categorical data. Results: The study revealed that 108(56.25%) knew about diabetes out of 192 diabetic patients. More than half, 142 (73.93%) patient knew the impact of diabetes on other organs. Sixteen (11.26%) said kidneys, 13(9.13%) as heart and 45(31.69%) said that diabetes affects multiple organs. Majority 142 (73.95%) of patients had knowledge of complications. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10057 Journal of Nobel Medical College Vol.3(1) 2014; 62-65